“La Conciencia lingüística léxica en la lectoescritura” . - Semblantes Changoluiza, Kevin Mauricio (2024)
The present research work presents the topic of lexical linguistic awareness in reading and writing, where it is the ability to analyze and work with language as an intellectual object, the use of language as a tool for communication, analysis and problem solving must be understood. The main objective of the study is the influence of the development of lexical linguistic awareness on reading and writing in second-year children of the “Luis Napoleón Dillon” Basic Education School through the implementation of flashcards to generate significant learning, which has a methodology with a qualitative approach because it seeks to focus on the individual to be able to interact and understand the problem in depth, the study of this problem is based on the descriptive method, the research was based on a documented and field basis, the technique used was observation and the instrument applied for data collection was an interview, the population was second year EGB students, children between 6 years old, the proposal of the research work was based on the development of flashcards focused on the phonological, lexical, semantic, syntactic components, to strengthen lexical linguistic awareness in the literacy process of children where the results of the study presented a trend. In conclusion, reading and writing are skills that constitute a fundamental pillar in the development process of children, however, several difficulties in reading and writing may arise when learning to read and write.